Tolerance Education in Local Cultural Wisdom Values (The Study At Ki Ageng Tarub Cultural Kirab, Tarub Village, Tawangharjo, Grobogan) - Ahmad Fauzi (2022)
Indonesia is a pluralistic country, with the motto